Effect of the critical care outreach team on patient survival to discharge from hospital and readmission to critical care: non-randomised population based study. Issue 7422 (30th October 2003) - Ball, Carol; Kirkby, Margaret; Williams, Susan
Abstract: Objectives To determine the effect of the critical care outreach team on patient survival to discharge from hospital after discharge from critical care and readmission to critical care. Design Non-randomised population based study. Setting Tertiary referral teaching hospital with 1200 beds. Participants Patients discharged from the critical care unit after their first or only admission for two study periods, 26 February 2000 to 25 February 2001 and 26 February 2001 to 25 February 2002. Main outcome measures Survival to discharge from hospital after discharge from critical care and readmission to critical care. Results The introduction of a critical care outreach team improved survival to discharge from hospital after discharge from critical care by 6.8% (risk ratio 1.08). Readmission to critical care decreased by 6.4% (0.48). Conclusions The activity of the critical care outreach team seems to improve patient survival to discharge from hospital and may reduce the number of readmissions to critical care.